Conceptual design model of Assistive Courseware for Low Vision (AC4LV) learners - Aziz, Nurulnadwan; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (2014)
This paper describes an ongoing study related to the design of conceptual design model which specific to learning content application for low vision learners.Reviews from literature s indicate that content application such as course ware which is specifically designed to cater the needs of low vision learners in learning is highly scarce.It was found that most of the existing content applications including courseware focus to the needs of normal student, in which most of this course ware mean too little to the low vision learners in terms of information accessibility, navigation ability, and pleasure aspects.In addition, the use of Assistive Technology (AT) such as magnifying glass was also problematic for them.Thus, this study aims at creating an alternative content application particularly courseware for low vision learners.It is called as Assistive Courseware for Low Vision (AC4LV).Prior to develop an AC4LV a specific design model has to be proposed as guidance for the developer to refer to.So, this paper proposes a Conceptual Design Model of AC4LV by utilizing three phases of activities.Future works is to validate the proposed model through expert review and prototyping method.